Characterization of LncRNA expression profile and identification of novel LncRNA biomarkers to diagnose coronary artery disease. (August 2018) - Li, Lin; Wang, Laiyuan; Li, Hongfan; Han, Xikun; Chen, Shufeng; Yang, Bin; Hu, Zunsong; Zhu, Huijuan; Cai, Can; Chen, Jichun; Li, Xiangdong; Huang, Jianfeng; et al.
Abstract: Background and aims: Dysregulation of long non-coding RNAs (lncRNAs) has been proven to be involved in the pathogenesis of coronary artery disease (CAD). However, it remains to be extensively explored. Thus, the present study aims to study expression patterns, biological functions, and diagnostic value of lncRNAs in CAD. Methods: Using microarray, we performed the transcriptome-wide lncRNA and mRNAs expression profile of peripheral blood mononuclear cells (PBMCs) of 93 CAD patients and 48 healthy controls. Gene Ontology (GO) and pathway analysis for differentially expressed mRNAs were used to investigate underlying biological associations of differentially expressed lncRNAs, and path-net was created to depict interactions of significant pathways. qRT-PCR was used to validate selected lncRNAs in 412 CAD patients and 295 healthy controls. Receiver operating characteristic (ROC) curve analysis was performed to evaluate whether lncRNAs could be used in the diagnosis of CAD patients. Finally, the functional significance of validated lncRNAs was determined in THP-1-derived macrophages. Results: We identified 1210 lncRNAs and 890 mRNAs differentially expressed from the expression profile and validated 7 lncRNAs. Two novel lncRNA biomarkers, ENST00000444488.1 and uc010yfd.1, together with CAD risk factors, had the better performance for discrimination of CAD patients from healthy controls, and ENST00000444488.1 could diagnose acute myocardial infarction (AMI) patients. The knockdown of 20 ENST00000444488.1, uc010yfd.1, ASO3973 and ENST00000602558.1 affected the expression of inflammation-related genes and their nearby genes in THP-1-derived macrophages, respectively. Conclusions: We offered a transcriptome-wide overview of aberrantly expressed lncRNAs in CAD patients, and identified two novel lncRNA biomarkers for diagnosing CAD. Loss of validated lncRNAs regulated the expression of inflammation-related genes and their nearby genes. Highlights: We offered a transcriptome-wide overview of aberrantly expressed lncRNAs in CAD patients. ENST00000444488.1 and uc010yfd.1 were identified as novel lncRNA biomarkers for diagnosing CAD. Loss of validated lncRNAs regulated the expression of inflammation-related and nearby genes in THP-1-derived macrophages.